EFFICIENCY OF THE FLOTATION COPROOVOSCOPICAL INTRAVITAL DIAGNOSTIC METHODS OF PROTOZOOSES AND NEMATODOSES OF PІGS - Yevstafieva, V. О. (Scientific Progress & Innovations, 2014)
Представлені результати визначення видового складу паразитозів свиней у господарствах Полтав- ської області (Полтавський, Диканський, Карлівський райони) та ефективності флотаційних методів їх діагностики. Внаслідок копроовоскопічних дослі- джень встановлені збудники гельмінтозів (аскароз, езофагостомоз, трихуроз) і протозоозів (еймеріози, балантидіоз). Флотаційні методи дослідження із застосуванням бішофіту та Котельникова-Хренова показали високу ефективність у процесі діагностики аскарозу, езофагостомозу, еймеріозів і балантидіозу відповідно. The results determine the species composition of parasites of pigs in the Poltava region (Poltava, Dykanka, Karlivka areas) and the efficiency of flotation methods of diagnosis. Because coproovoscopical studies established pathogens helminths (askarosis, ezofahostomosis, tryhurosis) and protozooses (eymerioses, balantidiasis). Flotation method using bishofit and method of the Kotelnikov-Khrenov showed high efficiency in diagnosis askarosis, ezophagostomosis, eymerioses and balantidiosis respectively.